Pengaruh Pendidikan terhadap Pertumbuhan Ekonomi: Kajian Literatur pada Negara Berkembang di Indonesia - Dimas Surya; Deni Dharmawansyah; Erwin Fitrah Jauhari; Khairina Tambunan (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
Article discusses the influence of education on economic growth in developing countries, with a special focus on Indonesia. Education is considered a key factor in improving the quality of human resources, which contributes to economic growth. The three main theories that explain this relationship are human capital theory, allocation theory, and class growth theory. Human capital theory suggests that higher education can increase productivity and wages, despite criticism regarding job quality. Allocation theory highlights the role of education in allocating individuals based on educational strata, while class growth theory highlights the impact of education on social inequality. In Indonesia, challenges faced in the education sector include inequality of access and poor infrastructure, especially in remote areas. Despite increasing education budgets, data shows that classroom infrastructure problems are still not fully resolved. This article emphasizes the importance of research and development to improve the quality of education, which in turn is expected to encourage economic growth and reduce social problems such as unemployment and crime. Successful examples from other countries, such as South Korea, show that a strong education system can contribute significantly to economic growth. The method used in this research is a literature review, which collects and analyzes various studies related to the influence of education on economic growth. The literature sources used include books, academic journals, and research reports, which allows the authors to gain a broader picture of trends, findings, and research gaps in this topic.